A DNA Vaccine Formulated with Chemical Adjuvant Provides Partial Protection against Bovine Herpes Virus Infection in Cattle - Quattrocchi, Valeria; Soria, Ivana; Langellotti, Cecilia Ana; Gnazzo, Victoria; Gammella, Mariela; Moore, Dadin P.; Zamorano, Patricia I. (Frontiers in Immunology, 2017)
Bovine herpesvirus – 1 (BoHV-1) is the causative agent of bovine infectious rinotracheitis, an important disease worldwide. Although conventional BoHV-1 vaccines, including those based on the use of modified live virus and also inactivated vaccines are currently used in many countries, they have several disadvantages. DNA vaccines have emerged as an attractive approach since they have the potential to induce both humoral and cellular immune response, nevertheless, it is largely known that potency of naked DNA vaccines is limited. We demonstrated previously, in the murine model, that the use of adjuvants in combination with a DNA vaccine against BoHV-1 is immunologically beneficial. In this study, we evaluate the immune response and protection against challenge elicited in bovines, by a DNA vaccine carrying the sequence of secreted version of glycoprotein D (gD) of BoHV-1 formulated with chemical adjuvants. Bovines were vaccinated with formulations containing the sequence of gD alone or in combination with adjuvants ESSAI 903110 or MontanideTM 1113101PR. After prime vaccination and 2 boosters, animals were challenged with infectious BoHV-1. Formulations containing adjuvants MontanideTM 1113101PR and ESSAI 903110 were both, capable of increase humoral immune response against the virus and diminish clinical symptoms. Nevertheless, only formulations containing adjuvant MontanideTM 1113101PR was capable of improve cellular immune response and diminish viral excretion. To our knowledge, it is the first time that a BoHV-1 DNA vaccine is combined with adjuvants and tested in cattle. These results could be useful to design a vaccine for the control of bovine rinotracheitis.